Assessment of myocardial adrenergic innervation with a solid-state dedicated cardiac cadmium–zinc–telluride camera: first clinical experience. (17th December 2013) - Gimelli, Alessia; Liga, Riccardo; Giorgetti, Assuero; Genovesi, Dario; Marzullo, Paolo
Abstract: Aims: To investigate the relationships between regional adrenergic innervation heterogeneity, myocardial perfusion, and contractile function obtained by means of a low-dose imaging protocol with a cadmium–zinc–telluride (CZT) dedicated camera. Methods: Twenty-eight patients with or without ischaemic heart disease underwent 123 I-metaiodobenzylguanidine (MIBG) planar scintigraphic and CZT early and delayed evaluations followed by 99m Tc-tetrofosmin rest gated CZT with a single-day protocol. The heart-to-mediastinum ratio and the washout rate were computed from planar 123 I-MIBG images. The summed 123 I-MIBG defect scores (SS-MIBG) were semi-quantitatively assessed from CZT images. The summed rest score (SRS), summed motion score (SMS), and summed thickening score (STS) were quantitated from 99m Tc-tetrofosmin images. Results: Sixteen patients showed a depressed left ventricular systolic function [ejection fraction (EF)<50%]. They presented higher SRS ( P = 0.007), SMS ( P < 0.001), STS ( P < 0.001), and early SS-MIBG ( P = 0.007) values than those with normal contractile function. Interestingly, higher early SS-MIBG values, index of regional sympathetic innervation heterogeneity, clustered with more elevated SRS ( P = 0.023), and more impaired measures of regional and global left ventricle systolic function, i.e. SMS ( P = 0.046), STS ( P = 0.014), and EF ( P = 0.027). At multivariate analysis, a higher SRS ( P = 0.039) remained the only independent predictor of more elevated early SS-MIBG values. In the 20 of 28 ischaemic patients, the correlations between early SS-MIBG and SMS ( P = 0.017) and also STS ( P = 0.036) were further confirmed. The effective dose of the investigation was 4.2 ± 0.72 mSv. Conclusions: An altered early SS-MIBG, assessed with a low-dose imaging protocol and a CZT cardiac camera, identifies patients with more impaired myocardial perfusion and contractile function.